PENGARUH MEDIA PEMBELAJARAN FILM DOKUMENTER “SUMPAH PEMUDA” TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK - Rizkya, Azzalfa Alifah; Damanhuri, Damanhuri; Fitrayadi, Dinar Sugiana (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to determine whether documentary film learning media has an impact on improving student learning outcomes in Pancasila Education subjects. A quasi-experimental quantitative approach was chosen in this study. The population comes from class VIII of Shohibul Baroque Junior High School. A total of 84 student populations were used in the sample. With details, 42 students of class VIII A were formed as an experimental class, while 42 students of class VIII B were formed as a control class who were not given treatment. The data collection tool was a multiple-choice questionnaire of 20 questions. Based on the results of research in the two groups, the results are normally distributed and homogeneous. The T-test is used in hypothesis testing to obtain results that have a significant effect on the use of documentary film learning media on the cognitive learning outcomes of grade VIII students. Based on the calculation results, the value of rcalculate sig (2-tailed) is 0.014 < rtable is 0.05. Thus H1 is accepted and Ho is rejected. This indicates that documentary film learning media affects the cognitive learning outcomes of grade VIII students in the National Awakening and Youth Pledge materials.